2019
DOI: 10.1136/emermed-2018-207872
|View full text |Cite
|
Sign up to set email alerts
|

Compliance with hand hygiene in emergency medical services: an international observational study

Abstract: IntroductionHealthcare-associated infection caused by insufficient hygiene is associated with mortality, economic burden, and suffering for the patient. Emergency medical service (EMS) providers encounter many patients in different surroundings and are thus at risk of posing a source of microbial transmission. Hand hygiene (HH), a proven infection control intervention, has rarely been studied in the EMS.MethodsA multicentre prospective observational study was conducted from December 2016 to May 2017 in ambulan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 15 publications
0
26
0
5
Order By: Relevance
“…Studies in the literature exploring which parts of the hand remain dirty or unclean after handwashing are scarce. Studies that have been carried out on the hand hygiene practices of healthcare workers and their compliance with these practices, however, have indicated that hand hygiene practices are insufficient and compliance is poor (Kelcikova, Skodova, & Straka, 2012; Kosucu, Göktas, & Yıldız, 2015; MacDonald, McKillop, Trotter, & Gray, 2006; Škodová et al, 2015; Vikke et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Studies in the literature exploring which parts of the hand remain dirty or unclean after handwashing are scarce. Studies that have been carried out on the hand hygiene practices of healthcare workers and their compliance with these practices, however, have indicated that hand hygiene practices are insufficient and compliance is poor (Kelcikova, Skodova, & Straka, 2012; Kosucu, Göktas, & Yıldız, 2015; MacDonald, McKillop, Trotter, & Gray, 2006; Škodová et al, 2015; Vikke et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…9,10 The overall compliance observed in the current study was similar to the data in the literature. [2][3][4][5][6][7] There was no evidence of improvement during the study period, which could be related to various factors including deficiencies in staff education, irregular feedback, and loss of timely analysis of compliance data. Another factor, one relevant to improvement, is the weak leadership support to the infection control recommendations.…”
Section: Discussionmentioning
confidence: 99%
“…A conformidade da higiene das mãos entre os prestadores foi notavelmente baixa, com maior conformidade após os contatos com os pacientes em comparação com antes dos contatos e dependência excessiva de luvas. Recomendamos mais pesquisas sobre desafios contextuais e percepções de higiene entre os profissionais para melhor compreensão da situação (VIKKE et al, 2019 de infecção e a taxa de adesão às boas práticas como a higiene das mãos e o uso de luvas (ROCK et al, 2013;ZOTTELE et al, 2017). As unidades de pronto socorro são consideradas críticas para a adesão à higiene das mãos, pois somam-se fatores como superlotação, carga de trabalho, falta de tempo e, muitas vezes, déficit de funcionários (CARTER, POUCH, LARSON, 2014;GRABOWSKI et al, 2018).…”
Section: Tabela -unclassified